Dampak Permainan Tradisional Gundu (Kelereng) terhadap Nilai Kerja Sama Mata Pelajaran Matematika - Nurmutia Herdiana, Anandea; Dantes, Nyoman; Parmiti, Desak Putu (Jurnal Pendidikan Matematika : Judika Education, 2026)
This study aims to analyze the potential impact of the traditional game of Gundu (marbles) on improving students' cooperation values, particularly in the context of mathematics learning, through a literature study approach. The integration of traditional games that are rich in ethnomathematics and social character values ​​is believed to be able to become an alternative approach in education. The results of the analysis show that the Gundu game not only contains mathematical concepts such as geometry and arithmetic operations, but also inherently trains students' social-emotional aspects, including cooperation, honesty, and sportsmanship, which can have a positive impact on group learning in mathematics. In conclusion, there is a positive and significant influence of the traditional game of Gundu (marbles) on students' cooperation values, which can be optimized in the context of mathematics learning.   Keywords: Traditional Gundu Game (Marbels), Mathematics, Cooperation Values